Effects of Postconditioning with Fructose on Arrhythmias and the Size of Infarct Caused by Global Ischemia and Reperfusion in Isolated Rat Heart - Jila Haghi; Tahereh Eteraf-Oskouei; Moslem Najafi (Tabriz University of Medical Sciences, 2018)
Purpose: In the present study, postconditioning effect of fructose against ischemia/reperfusion (I/R)-induced arrhythmias and infarct size were investigated in isolated rat heart. Methods: The isolated hearts were divided into 7 groups, mounted on a Langendorff apparatus at constant pressure then subjected to 30 min zero flow global ischemia followed by 120 min reperfusion. In the control group, normal Krebs-Henseleit (K/H) solution was perfused into the hearts throughout the experiment. In two separate sets of experiments, the treatment groups received 12, 24 and 48 mM of fructose with/without normal glucose in K/H solution for 20 min at the beginning of reperfusion. Cardiac arrhythmias including number of ventricular tachycardia (VT), total ventricular ectopic beats, incidence and duration of VT, reversible and irreversible ventricular fibrillation were recorded and analyzed during the first 30 min of reperfusion. Computerized planimetry method was used to determine volume and percentage of infarct size. Results: Administration of fructose as a postconditioning agent clearly reduced volume and percentage of infarct size in the all treatment groups. The effect was statistically significant especially in the hearts that treated by fructose plus glucose (P<0.05). However, fructose alone or its co-administration with glucose had no significant inhibitory effect against reperfusion arrhythmias. Conclusion: The results showed that perfusion of high concentration of fructose alone or coincident with glucose in globally ischemic-reperfused isolated rat hearts can reduce infarct size without inhibitory effect against reperfusion arrhythmias. Probably, fructose by providing adequate ATP for cardiac functions may inhibit necrosis and death of cardiomyocytes during I/R.